Building a Participatory Archive With an Australian Suburb: Case Study of Canberra’s Biggest Bogan Suburb, Kambah - Curham , Louise (Archives & Manuscripts, 2023)
Participatory appraisal and building archives with communities have been discussed amongst archivists across the world for decades. There is reportage on building community resources for and by Aboriginal and Torres Strait Islander communities, but there is less reportage on these endeavours with other communities. This reflection reports on building an archive with the community of Kambah, a suburb with a mixed reputation in the Canberra community. A challenge for participatory archives identified through this project was scale – if successful, the volume of content quickly becomes overwhelming. Another challenge is the responsibility that goes with accepting content from contributors. Expectations are set up that the content will be used or shared. And crucially, participation means everyone. Strategies are needed to connect with contributors that go beyond relationships in easy reach for the archivist based on existing connections. A final lesson comes from socially engaged art, a practice that focuses on community participation. This calls on the archivist to recognise their standpoint, the worldview they bring. Our sector has recognised that collections and building them is not neutral. For archivists, there remains much to do to work out how to meaningfully share that power and authority as collections are built.